2012
DOI: 10.1002/jmv.23313
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of immunity to tick‐borne encephalitis after vaccination and natural infection

Abstract: Long-term persistence of immunity was assessed in 66 patients who had contracted tick-borne encephalitis (TBE) and in 126 subjects who had completed primary TBE immunization using a conventional three-dose schedule from 3 to 8 years earlier. Immunity was tested in the subjects stratified by age as follows: ≤40 years (N = 37); 41-60 years (N = 100); and over 60 years (N = 55). Antibody levels decreased significantly with increasing age in the vaccinated cohort by comparison with the individuals who had previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…From the questionnaires we acquired information regarding previous tick-borne infections, general health status, and vaccination status for TBE as well as for yellow fever and Japanese encephalitis (Appendix S1). We included 8 health-related factors from the questionnaires in the analysis that we considered might influence the immune response; previous TBE disease [22], vaccination against other flaviviruses (yellow fever or Japanese encephalitis) [38], ≥2 tick-bites during the previous 3 months [39], pet-ownership (dog or cat) [40], asthma [41], smoking [42], allergy [43], and diabetes [44]. If a study participant visited health care for a suspected tick-borne disease during the 3-month study period we also investigated their medical records.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the questionnaires we acquired information regarding previous tick-borne infections, general health status, and vaccination status for TBE as well as for yellow fever and Japanese encephalitis (Appendix S1). We included 8 health-related factors from the questionnaires in the analysis that we considered might influence the immune response; previous TBE disease [22], vaccination against other flaviviruses (yellow fever or Japanese encephalitis) [38], ≥2 tick-bites during the previous 3 months [39], pet-ownership (dog or cat) [40], asthma [41], smoking [42], allergy [43], and diabetes [44]. If a study participant visited health care for a suspected tick-borne disease during the 3-month study period we also investigated their medical records.…”
Section: Methodsmentioning
confidence: 99%
“…Although age affects the quantitative antibody response, the quality of the antibodies appears unaffected by increased age [24]. In contrast to vaccination, individuals naturally infected with TBEV preserve high antibody titers throughout life [22]. Vaccine failures can occur in all ages, despite complete vaccination, but the majority of cases are among individuals over 50 years old [15], [25], [26].…”
Section: Introductionmentioning
confidence: 99%
“…They found that all three tests detected antibodies at a maximum of 4 months after the last vaccine dose and that there was a good correlation between the antibody titers. Baldovin et al [20] investigated the persistence of TBEV antibodies in vaccinated ( n  = 126) and naturally infected ( n  = 66) groups. Blood samples from participants in the vaccinated and natural infection groups were sampled 3–8 years after the last immunization and 1.4–13.7 years after viral infection, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Using a rapid schedule with the Encepur vaccine (days 0, 7, 21) in children has been shown to provide fast protection and stable antibody levels for at least 1 year [209]. The antibody response to TBEV vaccination declines with age [210][211][212][213][214][215][216], and older individuals are at higher risk of vaccine failures [189,200,217]. Both the European vaccines are considered safe to use and efficacious for individuals ≥1 years old by the WHO [201].…”
Section: Vaccinementioning
confidence: 99%